Giving Marital Assets From Wife's Family to Husband Through Marriage Reveals the Perspective of Bebesen District Ulama - Hikmah Amna Mnr; Ibnu Radwan Siddiq Turnip (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This article aims to examine the practice of giving marital property from the wife's family to the husband through angkap marriage in Tan Saril Village, Bebesen District, and how the perspective of Bebesen sub-district ulama on the practice of giving marital property through angkap marriage is still carried out by some people in the village.This research is an empirical legal research, with a legal sociological approach and qualitative data analysis. Primary data sources were obtained from interviews with communities who practice giving marital property from the wife's family to the husband through angkap marriage and interviews with scholars of Bebesen sub-district. The results showed that there are still some communities in Tan Saril Village, Bebesen District, who practice giving marital property from the wife's family to the husband through angkap marriage, where the property will be given to the husband in the form of agricultural land, provided that the husband is drawn into the wife's family clan. If there is a divorce due to a dispute, not due to death, then the property is returned to the wife. Some scholars of Bebesen sub-district argue that the provision of property grants through angkap marriage is something that is permissible but better not done, because it can cause losses to one party. Some scholars consider this only applies to customary law, and is not in accordance with the principle of covenant in Islam which requires clarity in a contract.